Kinematics Modeling and Analysis of Manipulator based on Dual Quaternion - 葛为民; 宇旭东; 王肖锋; 邢恩宏 (Jixie chuandong)
To simplify the kinematics expression and to increase the motion response speed for manipulators,a kinematics modeling method is proposed based on dual quaternion. First,to reduce the computational amount,the general equation of the forward kinematics of the manipulator is presented using dual quaternion.Then,to solve the inverse kinematics problem of the assembled joint variables of manipulator,the sub-problems are classified into two groups of uniaxial and biaxialox,this classification method includes the existing sub-problem classification,which is beneficial to the joint variable grouping solution. Finally,taking a 6 R series manipulator as an example,the forward kinematics and inverse kinematics modeling and simulation analysis based on the dual quaternion are carried out. The results show that this method is effective,comparing with the spinor method,its calculation time of forward kinematics is reduced by about 30%,the geometric meaning of inverse kinematics is more clear. This method can be applied to other sub-problems solution of the manipulator configuration.